Empowerment of the School Literacy Movement (GeLiS) at State Elementary School 5 Saparan - Nindy Citroresmi Prihatiningtyas; Mariyam Mariyam; Zulfahita Zulfahita; Dina Anika; Sri Mulyani (STKIP Singkawang, 2022)
GeLiS is an effort in the form of participatory activities involving school residents so that students get used to reading. The literacy skills of students in Kumba Village are sufficient. Based on the preliminary study, the library that should be used as a place to read books is only used as a place to store books. So with this GeLiS, it is hoped that students' reading literacy skills will increase. This activity aims to provide teachers with an understanding of GeLiS and provide examples of the implementation that teachers must do to support the literacy movement in elementary schools. The method used is the lecture method and questions and answers about the literacy movement in schools. The results of this activity indicate that the teacher's understanding of the literacy movement in elementary schools is good, and adapted to the abilities of students, while the implementation that teachers do in grade IV is still monitoring to improve reading and writing skills and to increase self-confidence through listening to the national compulsory anthem. , take turns reading picture story books provided in the reading corner and library.